Influence of Biodynamic Compost and Its Wash on Rice Growth and Yield - Arvind Kumar Shukla; Ram Ratan Singh; Tripti Mishra; Kaushlendra Mani Tripathi; Shwetank Shukla; Subedar Singh (Current Research Progress in Agricultural Sciences Vol. 10, 2025)
Pioneering a sustainable approach to waste management and organic farming by leveraging Bio Dynamic Conversion (BDC) technology. This initiative transforms biodegradable waste such as leaves, village waste, and biowaste into high-quality bio dynamic compost within 14 days. Additionally, the investigation focuses on providing fresh and organic food to individuals while ensuring the preservation of surplus food through advanced dehydration technology, reducing wastage and enhancing food security. The present investigation was conducted in the Kharif of 2021–2022 at the Student’s Instructional Farm at the A.N.D. University of Agriculture & Technology, Kumarganj, Ayodhya (U.P.). The experiment was laid out in Randomized Block Design, replicated thrice, having 8 treatments i.e. T1 (Absolute Control), T2 (Biodynamic compost 1q/ha + 50 % RDF), T3 (Biodynamic compost 2 q/ha + 50 % RDF), T4 (T2 + Root dipping with Biodynamic compost wash 10 ml/ lit of water), T5 (T3 + Root dipping with Biodynamic wash 10 ml/lit of water), T6 (T2 + foliar application of Biodynamic compost wash of 10 ml/10 lit of water), T7 (T3 +foliar application of Biodynamic compost wash of 10 ml/ lit of water), T8 (100 % RDF. Results revealed that the highest growth attributes viz., Plant height, maximum dry matter accumulation, highest number of tiller (m-2), Panicle length, number of grain per panicle and test weight (gm), maximum grain yield (q ha-1), highest straw yield, maximum biological yield (q ha-1) and maximum harvest index (q ha-1) was recorded significantly over rest of the treatments in T7 (T3 +foliar application of Bio dynamic compost wash of 10 ml/ lit of water) while it recorded lowest in in T1 (absolute control) during the investigation. In conclusion, by turning waste into wealth, supporting farmers, and ensuring sustainability, it creates a profitable and scalable business model. With expert guidance and cutting-edge technology, it was poised to revolutionize waste management and organic farming.